Predicting recurrence of hepatocellular carcinoma after liver transplantation using a novel model that incorporates tumor and donor‐related factors. (9th December 2021) - Orci, Lorenzo A.; Combescure, Christophe; Fink, Michael; Oldani, Graziano; Compagnon, Philippe; Andres, Axel; Berney, Thierry; Toso, Christian
Summary: Evidence suggests that liver graft quality impacts on posttransplant recurrence of hepatocellular carcinoma (HCC). As of today, selection criteria only use variables related to tumor characteristics. Within the Scientific Registry of Transplant Recipients, we identified patients with HCC who underwent liver transplantation between 2004 and 2016 (development cohort, n = 10 887). Based on tumor recurrence rates, we fitted a competing‐risk regression incorporating tumor‐ and donor‐related factors, and we developed a prognostic score. Results were validated both internally and externally in the Australia and New Zealand Liver Transplant Registry. Total tumor diameter (subhazard ratio [sub‐HR] 1.52 [1.28–1.81]), alpha‐feto protein (sub‐HR 1.27 [1.23–1.32], recipient male gender (sub‐HR 1.43 [1.18–1.74]), elevated donor body mass index (sub‐HR 1.26 [1.01–1.58]), and shared graft allocation policy (sub‐HR 1.20 [1.01–1.43]) were independently associated with tumor recurrence. We next developed the Darlica score (sub‐HR 2.72 [2.41–3.08] P < 0.001) that allows identifying risky combinations between a given donor and a given recipient. Results were validated internally ( n = 3 629) and externally in the Australia and New Zealand Liver Transplant Registry ( n = 370). The current score is based on variables that are readily available at the time of graft offer. It allows identifying hazardous donor–recipient combinations in terms of risk of tumor recurrence and overall survival. Abstract : We constructed a risk‐scoring tool informing decision making upon allocating human liver grafts to patients hepatocellular carcinoma.